Long term performance of cross-border M&As : empirical analysis of non-US banks for 1985-2001. - Hua, Mei Yen. (2008)
Our study examines the long-term performance of non-UScross-border banking mergers and acquisitions, while addressingmethodological issues relevant to the study of non-US bank mergers andacquisitions. This study finds that for the 106 non-US mergers andacquisitions, the abnormal returns are not statistically significant inone-year and three-year horizons.